2000
DOI: 10.1093/ajcn/71.4.914
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial chylomicrons and VLDLs in severe hypertriacylglycerolemia are lowered more effectively than are chylomicron remnants after treatment with n−3 fatty acids

Abstract: n-3 Fatty acids effectively lower chylomicrons and VLDLs, but their effect on chylomicron remnants was observed only in the late postprandial phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 35 publications
0
32
1
Order By: Relevance
“…Interestingly, the latter level of energy expenditure is comparable with the energy expended during exercise in the present study [3.4 (0.2) MJ (fasting study group) or 3.2 (0.3) MJ (postprandial study group)], supporting the present finding that mechanisms other than increased LPL-mediated TG clearance may be implicated in the attenuation of TG by prior exercise, particularly when modest levels of exercise are performed. This dissociation between changes in TG concentrations and changes in LPL activity does not appear to be unique to exercise-induced effects; decreases in TG concentrations elicited by dietary supplementation with n-3 polyunsaturated fatty acids may also be mediated by factors other than an increase in post-heparin LPL activity (Weintraub et al 1988;Nozaki et al 1991;Westphal et al 2000).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the latter level of energy expenditure is comparable with the energy expended during exercise in the present study [3.4 (0.2) MJ (fasting study group) or 3.2 (0.3) MJ (postprandial study group)], supporting the present finding that mechanisms other than increased LPL-mediated TG clearance may be implicated in the attenuation of TG by prior exercise, particularly when modest levels of exercise are performed. This dissociation between changes in TG concentrations and changes in LPL activity does not appear to be unique to exercise-induced effects; decreases in TG concentrations elicited by dietary supplementation with n-3 polyunsaturated fatty acids may also be mediated by factors other than an increase in post-heparin LPL activity (Weintraub et al 1988;Nozaki et al 1991;Westphal et al 2000).…”
Section: Discussionmentioning
confidence: 95%
“…However, it has been suggested that increased dietary LC n-3 PUFA may alter the binding affinity of the insulin receptor and improve glucose transport into cells via glucose transporters (Vessby, 2000). The hypotriacylglycerolaemic effects of LC n-3 PUFA are believed to be the result of a combination of suppressed production and secretion of hepatically-derived TAG and an accelerated rate of TAG clearance from the circulation (Westphal et al 2000). It has also been suggested that LC n-3 PUFA may markedly reduce plasma TAG by stimulating an increase in LPL activity.…”
Section: Pufa and Insulin Actionmentioning
confidence: 99%
“…These observations suggest that a mechanism other than increased LPL activity is the primary determinant of the TG-lowering effect of prior moderate exercise, and this effect is then modulated by a more inconsistent effect of exercise on LPL. This dissociation between changes in TG and changes in LPL is not unique to exercise; TG decreases elicited by dietary supplementation with n-3 polyunsaturated fatty acids also appear to be mediated by factors other than increased LPL activity [90][91][92]. In addition to the above reports demonstrating that exercise-induced changes to TG and LPL may be dissociated, other studies have shown that TG reductions following exercise can occur in the absence of increased TG clearance.…”
Section: Evidence For Mechanisms Other Than Increased Tg Clearancementioning
confidence: 92%